Performance features of virus removal filters with novel regenerated cellulose hollow fiber membranes - Tomoko Hongo-Hirasaki; Hiroki Fukutomi (iScience)
Summary: Virus removal filtration during the manufacturing process plays an essential role in ensuring the virus safety of biologics. Following the revision of International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) Q5A, the guidelines for the virus safety of biopharmaceuticals now state that an effective viral clearance process should achieve a viral reduction of 4 log10 or greater. Technological advances in the development of new manufacturing technologies for continuous production and the development of next-generation antibody drugs have increased the need for virus removal filters suited to a variety of applications. The newly available virus removal filter, Planova S20N, incorporates a newly developed regenerated cellulose hollow fiber membrane. In addition to stable filtration of a variety of antibody solutions, this filter demonstrates robust parvovirus removal under a variety of filtration operating conditions, including low flow rate filtration for continuous process.